Germ cell depletion using HSV-TK in mouse testes - Constance Dollet; Miyuki Shindo; Shun Takahashi; Kento Ito; Tomoo Eto; Toshiaki Watanabe (Scientific Reports)
Abstract Germ cell transplantation is useful for the study of male germ cells and the generation of genetically modified animals. For transplantation, germ cell-free hosts generated using anticancer drug treatment, irradiation exposure, or genetic mutation are required. In this study, we aimed to develop a new system for germ cell depletion, more in compliance with the “3R” principles. For this purpose, we generated knock-in mice expressing a subtype of the herpes simplex virus type 1 thymidine kinase (HSV-TK30), reported to not induce infertility, unlike the original HSV-TK gene. Ganciclovir injection resulted in nearly complete abrogation of spermatogenesis. Furthermore, transplanted spermatogonial stem cells were differentiated into sperm in the host testes, and they gave rise to offspring. Therefore, the mice developed in this study enable the efficient removal of germ cells for germ cell transplantation in a manner more compliant with the 3R principles.